Trouble on the far right : contemporary right-wing strategies and practices in Europe - Fielitz, Maik; Laloire, Laura Lotte (Zheng zhi xue lun cong, 2016)
In Europe, the far right is gaining momentum on the streets and in parliaments. By taking a close look at contemporary practices and strategies of far-right actors, the present volume explores this right-ward shift of European publics and politics. It assembles analyses of changing mobilization patterns and their effects on the local, national and transnational level. International experts, among them Tamir Bar-On, Liz Fekete, Matthew Kott, and Graham Macklin, scrutinize new forms of coalition building, mainstreaming and transnationalization tendencies as aspects of diversified far-right politics in Europe.